Urban Transport Supervision by the Padang Transportation Agency under Mayor Regulation No. 42/2022 - Serena Desy Brezki; Adil Mubarak (Darul Yasin Al Sys, 2026)
Urban public transportation supervision is essential for ensuring passenger safety, service quality, and regulatory compliance. However, studies examining the implementation of supervision under Padang Mayor Regulation Number 42 of 2022 remain limited. This study aims to analyze the implementation of urban public transportation supervision by the Padang City Transportation Agency and identify the factors influencing its effectiveness. A qualitative descriptive approach was employed, with informants selected through purposive sampling, including transportation agency officials, drivers, vehicle owners, and service users. Data were collected through interviews and documentation and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that supervision has been implemented through observation, periodic inspections, and reporting activities. Nevertheless, its implementation has not been fully effective because supervisory activities remain largely situational rather than routine, systematic, and comprehensive, while operational and administrative violations continue to occur. The factors influencing supervision include environmental changes, organizational complexity, operational violations, and the need for delegated authority. This study concludes that strengthening observation mechanisms, regular inspections, inter-unit coordination, and integrated reporting systems is necessary to improve the effectiveness and sustainability of urban public transportation supervision in Padang City. Theoretically, this study contributes to the literature on transportation governance and regulatory implementation at the local government level. Practically, it provides policy implications for improving supervisory practices and strengthening institutional accountability in urban public transportation management.